Friction spot lap joining of aluminum alloy AA6061 to pre-holed and threaded carbon steel AISI 1006 - Ibrahim, H.K.; Hussein, Sabah Khammass; Jadee, Khudhayer (Zielona Góra: Uniwersytet Zielonogórski)
This work addresses to joining aluminum alloy AA6061 to carbon steel AISI 1006 sheets using the friction spot joining technique. The steel sheets were pre-holed and threaded with an internal M6 thread. The joining process was carried out by extruding the aluminum through the steel hole and thread using a rotating tool with friction between the tool and aluminum.
Keywords: AA6061; AISI 1006; friction spot joining; aluminum extrusion